Optimalisasi Keuntungan Banapuff dengan Metode Simpleks - Safitri, Reza; Utomo, Pradita Eko Prasetyo; Iftita, Hasanatul (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The growth of micro, small and medium enterprises (UMKM) makes business actors want to optimize profits. The limitations of raw materials and resources encourage business actors to review their strategies in order to generate optimal profits. The main purpose of the study is to calculate the optimal profit from the banapuff business and provide business strategic recommendations for the combination of products produced in order to generate optimal profits. The calculation of optimal profit will use linear programming with the simplex method, because the simplex method can confuse optimization calculations with many variables and constraints. The results of the study show that UMKM businesses can increase production profits by RP380,000.00 per production with the provision of producing 57.5 puffed bananas, 12.5 chocolate bananas and 20 sesame chocolate bananas. With this result, it is hoped that business actors will get a new business strategy in the efficiency of raw materials and the combination of product production through a systematic approach.